Factors predicting general health concerns and atypical behaviours in children with prenatal alcohol exposure and other adverse exposures - MacEachern, Sarah J.; Kar, Preeti; Nakhid, Daphne; Mitevska, Elena; Tortorelli, Christina; Forkert, Nils D.; Lebel, Catherine; McMorris, Carly A.; Gibbard, W. Ben (Frontiers in Pediatrics, 2023)
Background: Prenatal alcohol exposure (PAE) can have significant negative consequences on the health outcomes of children. Children with PAE often experience other prenatal and postnatal adverse exposures. Increased rates of general health concerns and atypical behaviours are seen in both children with PAE as well as with other patterns of adverse exposures, although these have not been systematically described. The association between multiple adverse exposures and adverse health concerns and atypical behaviours in children with PAE is unknown. Methods: Demographic information, medical history, adverse exposures, health concerns, and atypical behaviours were collected from children with confirmed PAE (n=22; 14 males, age range=7.9-15.9 years) and their caregivers. Support vector machine learning classification models were used to predict the presence of health concerns and atypical behaviours based on adverse exposures. Associations between the sums of adverse exposures, health concerns, and atypical behaviours were examined using correlation analysis. Results: All children experienced health concerns, the most common being sensitivity to sensory inputs (64%; 14/22). Similarly, all children engaged in atypical behaviours, with atypical sensory behaviour (50%; 11/22) being the most common. Prenatal alcohol exposure was most important factor for predicting some health concerns and atypical behaviours, and alone and in combination with other factors. Simple associations between adverse exposures could not be identified for many health concerns and atypical behaviours. Conclusion: Children with PAE and other adverse exposures experience high rates of health concerns and atypical behaviours. This study demonstrates the complex effects of multiple adverse exposures on health and behaviour in children.